2015
DOI: 10.1093/ndt/gfv361
|View full text |Cite
|
Sign up to set email alerts
|

A review of direct-acting antivirals for the treatment of hepatitis C in patients with advanced chronic kidney disease

Abstract: Historically, standard treatment of hepatitis C virus (HCV) infection in patients with renal impairment has been limited by low cure rates and poor tolerability. The introduction of direct-acting antivirals (DAAs) has revolutionized the treatment of HCV with impressive cure rates >90% and low rates of adverse events. Despite these major advancements, treatment of patients with HCV and advanced chronic kidney disease (CKD) is a major challenge due to the lack of efficacy and safety data in this patient populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…We considered studies involving adult patients aged 18 years or more, classified as patients with severe Renal impairment or CKD of stage 4 or 5 in which GFR is equal to or less than 30ml/min/1.73m 2 and less than 15ml/min/1.73m 2 , respectively. Both set of participants with ESRD whether on hemodialysis or not, were considered.…”
Section: Types Of Participantsmentioning
confidence: 99%
“…We considered studies involving adult patients aged 18 years or more, classified as patients with severe Renal impairment or CKD of stage 4 or 5 in which GFR is equal to or less than 30ml/min/1.73m 2 and less than 15ml/min/1.73m 2 , respectively. Both set of participants with ESRD whether on hemodialysis or not, were considered.…”
Section: Types Of Participantsmentioning
confidence: 99%
“…Most of the currently available all-oral regimens (i) were not evaluated in randomized controlled trials in patients with abnormal kidney function, (ii) are not optimal for patients with patients because they include ribavirin, which is associated with anaemia, or (iii) they contain drugs whose metabolites are cleared by the kidney (such as sofosbuvir). 10 Elbasvir (EBR, NS5A inhibitor)/grazoprevir (GZR, NS3/4A protease inhibitor) were recently studied in the C-SURFER (Hepatitis C: Study to Understand Renal Failure's Effect on Responses) study, a phase 2/3 double-blind, placebo-control trial in HCV genotype 1 patients with CKD4/5. 11 The study demonstrated that a once-daily oral regimen of EBR/GZR for 12 weeks was safe and can achieve high rates of SVR across many CKD patient subgroups, including those receiving haemodialysis.…”
Section: Introductionmentioning
confidence: 99%
“…The evolution from IFNbased therapy to DAAs is a remarkable accomplishment of the last decade and offers the possibility of life-saving treatment for millions of patients. 50,51 DAAs Sofosbuvir Sofosbuvir is a nucleotide analog NS5B polymerase inhibitor that targets the nonstructural protein 5B RNAdependent RNA polymerase, thus effectively terminating viral replication ( Figure 1, Table 1). Sofosbuvir is a prodrug that is phosphorylated into the active metabolite GS-461203, with subsequent dephosphorylation into the inactive metabolite GS-331007.…”
Section: Daa Agents In Patients With Ckdmentioning
confidence: 99%